Effect of second-phase particles on the oxidation behaviour of a high-manganese austenitic heat-resistant steel. (15th April 2021) - Liu, T.L.; Zheng, K.H.; Lin, Y.F.; Luo, Z.C.
Graphical abstract: Highlights: The SMC exhibits superior oxidation and spallation resistance. The scale formed on SMC is compact and consist of complex inter-overlapped oxides. The accelerated outward diffusion of Mn enhanced the oxidation resistance of SMC. The preferentially oxidised particles key the scale to improve the spallation resistance. Abstract: In this work, the presence of second-phase particles was found can significantly improve the oxidation and spallation resistances of a high-manganese austenitic heat-resistant steel. We show this unexpected improvement is originated from three correlated phenomena caused by the second-phase particles. First, the stratified growth of scale is avoided due to the chemical inhomogeneity of the novel steel. Further, the selective oxidation of second-phase particles provides a pinning effect for the scale. Last but not least, the accelerated outward diffusion of Mn reduces the critical Cr concentration for the formation of a stable protective Cr2 O3 layer.